Mission to Mars : my vision for space exploration - Aldrin, Buzz.; David, Leonard (Washington, D.C. : National Geographic, 2015)
Buzz Aldrin speaks out as a vital advocate for the continuing quest to push the boundaries of the universe as we know it. As a pioneering astronaut who first set foot on the moon during mankind's first landing of Apollo 11-- and as an aerospace engineer who designed an orbital rendezvous technique critical to future planetary landings -- Aldrin has a vision, and in this book he plots out the path he proposes, taking humans to Mars by 2035. --
Foreword / Andrew Aldrin -- The view from Air Force One -- Time for decision-making : call for a unified space vision -- Your space : building the business case -- Dreams of my moon -- Voyage to Armageddon -- The march to Mars -- Homesteading the red planet -- The clarion call -- Afterword: beyond here and now -- Changing visions for space exploration.
"With a new essay on space in our future" -- from cover.
Includes index.
Keywords: Space colonies; Space flight to Mars; Mars (Planet) -- Exploration; Mars probes; Print books